A note on the effect of dithiothreitol (DTT) on the depolarization of isolated sympathetic ganglia by carbachol and bromo-acetylcholine. - Brown, D A (1976)
The S-S reducing agent, dithiothreitol (DTT) altered the properties of nicotinic receptors in rat superior cervical ganglia such that (i) carbachol became less active as a depolarizing agent and (ii) bromo-acetylcholine produced an irreversible depolarization. The latter was temporarily annulled by hexamethonium (which retained antagonist properties), but returned when hexamethonium was removed. It is concluded that ganglionic nicotinic receptors might be quite similar to those for monoquaternary agonists in leech dorsal muscle.